Assessment of Procalcitonin to Predict Outcome in Hypothermia-Treated Patients after Cardiac Arrest - Pascal Stammet; Yvan Devaux; Francisco Azuaje; Christophe Werer; Christiane Lorang; Georges Gilson; Martin Max (Critical Care Research and Practice)
Objective. Determine the potential of procalcitonin (PCT) to predict neurological outcome after hypothermia treatment following cardiac arrest. Methods. Retrospective analysis of patient data over a 2-year period. Mortality and neurological outcome of survivors were determined 6 months after cardiac arrest using the Cerebral Performance Category (CPC) score. Results. Data from 53 consecutive patients were analyzed. Median age was 63 (54–71) and 79% were male. Twenty-seven patients had good outcome (CPC ≤ 2) whereas 26 had severe neurological sequelae or died (CPC 3–5). At 48 h, after regaining normothermia, PCT was significantly higher in patients with bad outcome compared to those with good outcome: 3.38 (1.10–24.48) versus 0.28 (0–0.75) ng/mL (𝑃<0.001). PCT values correlated with bad neurological outcome (𝑟=0.54, 𝑃=0.00004) and predicted outcome with an area under the curve of 0.84 (95% CI 0.73–0.96). A cutoff point of 1 ng/mL provided a sensitivity of 85% and a specificity of 81%. Above a PCT level of 16 ng/mL, no patient regained consciousness. PCT provided an additive value over simplified acute physiology score II. Conclusions. PCT might be an ancillary marker for outcome prediction after cardiac arrest treated by induced hypothermia.